Whey protein supplementation in muscle hypertrophy. (24th June 2020) - Sobral, C; Gomes, D; Silva, M; Martins, P; Baltazar, A
Abstract: Introduction The nutritional intake in the context of a hypertrophy training can affect body composition, the increase of muscle mass and strength. Whey protein seems to promote a reduction in body fat, improve hypertrophy, and other potential health benefits. This protein is one of the highest quality proteins due to its amino acid content (especially leucine) and to the rapid digestibility. Whey protein consumption has a robust ability to stimulate muscle protein synthesis. There are 3 types of whey protein: controlled, insulated and hydrolysed. Objectives The goal of this research is verifying the efficacy of the use of whey protein supplementation in athletes seeking muscle strength and mass gain. Methodology * We analysed scientific articles from 2014 to 2019, based on Pubmed and Google scholar. Keywords such as whey protein, supplement, hypertrophy, muscle mass and nutrition were used. Results From scientific research, six articles were analysed. Thus, it is estimated the analysis of 13 men under the age of 18 years and under 30 years of age. Only men with a percentage of fat mass less than or equal to 23% were selected. Two groups were created: the control group that consumed carbohydrate supplements and the experimental group that consumed 36g/day whey protein. Both groups performed 3 sessions/week of resistance training, and the used dose of protein derived from the diet was 1.4g/Kg/day. Both groups experienced gains in strength, 1 maxi (RM) and fat-free mass (FFM). However, the experimental group had an extra 9% and 27% in 1RM and FFM respectively compared to the control group. Conclusion In short, supplementation with whey protein contributes to the increase of muscle mass and strength in athletes whose training (frequency, volume and duration) and diet are suitable for this purpose.